1987
DOI: 10.2527/jas1987.641254x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Development, Daily Sperm Production and Epididymal Sperm Reserves in 15-mo-old Angus and Hereford Bulls: Effects of Bull Strain Plus Dietary Energy

Abstract: Bull calves (n = 143) were obtained from two strains of Angus and two strains of Hereford cattle for which replacements were selected on the basis of superior feedlot growth performance on either high- or medium-energy diets. From weaning to slaughter at 15 mo of age, bulls were fed either the high-energy (80% grain + 20% forage) or medium-energy diet (100% forage) corresponding to their strain. Bulls in high-energy diet groups had a greater (P less than .05) scrotal circumference at 12 mo, but not 15 mo of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…For example, in the experiment by Van Demark and colleagues, the 'low' plane of nutrition had little effect on body weight, as well as testicular size, even over 12 months, although production of spermatozoa was reduced . In the other cases, the 'high' planes seemed to constitute overfeeding, as the sperm production was markedly decreased compared to 'medium' or 'low' planes (Coulter et al, 1987;Mwansa and Makarechian, 1991). In addition, the energy and protein balance of the experimental diets requires clarification, as both have been manipulated in these studies, but not compared in the one experiment.…”
Section: Nutrition and The Production Of Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the experiment by Van Demark and colleagues, the 'low' plane of nutrition had little effect on body weight, as well as testicular size, even over 12 months, although production of spermatozoa was reduced . In the other cases, the 'high' planes seemed to constitute overfeeding, as the sperm production was markedly decreased compared to 'medium' or 'low' planes (Coulter et al, 1987;Mwansa and Makarechian, 1991). In addition, the energy and protein balance of the experimental diets requires clarification, as both have been manipulated in these studies, but not compared in the one experiment.…”
Section: Nutrition and The Production Of Spermatozoamentioning
confidence: 99%
“…As mentioned above, the Kastelic laboratory has added an extra level of sophistication to our understanding of the effects of nutrition over the first 18 months of life (review: Barth et al, 2008). However, after the period of rapid growth has ended, there appears to be little or no response to nutrition (Flipse and Almquist, 1961;Coulter et al, 1987). Caution is needed with these older studies on mature bulls.…”
Section: Nutrition and The Production Of Spermatozoamentioning
confidence: 99%
“…Young bulls attaining satisfactory-classification on a prebreeding BSE would therefore presumptively be expected to advance in physical and reproductive capability. However, environmental and physiological stressors are known to unfavorably influence some physical and seminal characteristics [17][18][19][20][21]. Factors such as season, climatic temperatures, toxic principles, disease and injury, physiologic stress and nutritional imbalances have been linked with alterations in scrotal circumference and seminal quality [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…Bailey et al (1991) reported no significant sire by diet interaction for growth rate and feed efficiency. However, Coulter et al (1987) reported a diet x breed interaction (PC0.05) for body weight at 12 and 15 months of age in Angus and Hereford bulls fed either a high or medium energy diets.…”
Section: Resultsmentioning
confidence: 99%